Multiscale pore damage evolution and self-inhibition mechanism in rock after dynamic impact: a coupled statistical constitutive model integrating loading effects - She, Haicheng; Liang, Yanxu; Liu, Siqi; Hu, Zaiqiang (Frontiers in Earth Science, 2025)
Impact disturbance, scanning electron microscopy, nuclear magnetic resonance, and triaxial compression tests were carried out to reveal the damage evolution law of rock after different numbers of impacts. The relationship between the energy spectrum area and porosity was determined. Combining the Weibull distribution and the Drucker–Prager intensity criterion, a rock statistical damage model and a constitutive model considering impact disturbance were established. Research has shown that (1) With increased numbers of impacts, different types of pores increased. Among these, the increase in mesopores and macropores was relatively greater than the increase in micropores. The porosity and expansion rate both increased significantly. However, their growth rate slowed with the increase in the number of impacts. This indicates that mesopores and macropores had a buffering effect on the impact of the disturbance effect. (2) As the number of impacts increased, the initial shear strength decreased rapidly, indicating that the disturbance development of pores and cracks had a significant deterioration effect on the mechanical properties of rocks. Subsequently, the decrease in shear strength slowed, indicating that the growth and development of pores and cracks also had an inhibitory effect on impact disturbance.